2018
DOI: 10.1016/j.yjmcc.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes constrict blood vessels after myocardial ischemia

Abstract: No-reflow phenomenon is defined as the reduced blood flow after myocardial ischemia. If prolonged it leads to profound damages in the myocardium. The lack of a detailed knowledge about the cells mediating no-reflow restricts the design of effective therapies. Recently, O'Farrell et al. (2017) by using state-of-the-art technologies, including high-resolution confocal imaging in combination with myocardial ischemia/reperfusion mouse model, reveal that pericytes contribute to the no-reflow phenomenon post-ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Despite being the second most abundant cell type in the heart after endothelial cells, pericytes retain similar roles as in the brain, including regulation of angiogenesis, barrier potential and selectivity and regulation of capillary blood flow . As in the brain, constriction of pericytes has been implicated in the context of myocardial infarction where ischaemia causes a powerful constriction to occlude capillaries, which intriguingly can be overcome using intravenous administration of adenosine . Interestingly, cardiac pericytes may also contribute to the origin of a myocardial infarction through their potential involvement in the development of atherosclerosis and vessel stiffening .…”
Section: Pericytes and Capillary Blood Flowmentioning
confidence: 99%
“…Despite being the second most abundant cell type in the heart after endothelial cells, pericytes retain similar roles as in the brain, including regulation of angiogenesis, barrier potential and selectivity and regulation of capillary blood flow . As in the brain, constriction of pericytes has been implicated in the context of myocardial infarction where ischaemia causes a powerful constriction to occlude capillaries, which intriguingly can be overcome using intravenous administration of adenosine . Interestingly, cardiac pericytes may also contribute to the origin of a myocardial infarction through their potential involvement in the development of atherosclerosis and vessel stiffening .…”
Section: Pericytes and Capillary Blood Flowmentioning
confidence: 99%
“…Which signaling molecules are needed to activate the extension of pericyte processes into the adjacent endothelial bed? And which signaling molecules are important for these pericytes to reverse the vasodilation that occurs after pericyte death [84]? Although Berthiaume and colleagues have revealed how pericytes respond to the deletion of a neighboring pericyte, they did not explore the molecular and cellular mechanisms involved in this process.…”
Section: Pericyte Communication With Other Tissue Components In Theirmentioning
confidence: 99%
“…Based on those initial criteria, it was suggested that mesenchymal stem cells have a common origin. Due to the broad organ distribution of mesenchymal stem cells, the attention had turned to pericytes as candidates to be the mesenchymal stem cells . Mesenchymal stem cells/pericytes have been shown to be heterogeneous in the skin and differ in their functions as well .…”
Section: Perspectives/future Directionsmentioning
confidence: 99%